KARAKTERISTIK INTEROGATIVA DALAM BAHASA MINANGKABAU DI KECAMATAN KOTO TANGAH KOTA PADANG - Libriani, Efany; Agustina, Agustina; Juita, Novia (Jurnal Bahasa dan Sastra, 2017)
The purpose of this study was to describe the form, the type and the function of the interrogative in Minangkabau language at Koto Tangah district, Padang city. This research is descriptive qualitative research method. The object of this research are the interrogative from people that live at Koto Tangah district, Padang city. Data analysis was performed with (1) transcripts of recording data into written language, (2) analyzing the data, (3) to classify the data into the aspects studied, (4) interpreting the data accordance with the purposes of the study, (5) make the conclusion. The result of this research, there are 40 interrogatives that found in Minangkabau language at Koto Tangah district, Padang city. There are 11 prototype interrogatives in Minangkabau language at Koto Tangah district, Padang city. Then, there are 26 derivative type interrogatives in Minangkabau language at Koto Tangah district, Padang city. Then, there are 3 bound type interrogatives in Minangkabau language at Koto Tangah district, Padang city. There are 11 types of interrogatives in Minangkabau language at Koto Tangah district, Padang city, they are (1) interrogative about noun, (2) interrogative about nominal, (3) interrogative about process, (4) interrogative about time, (5) interrogative about suppression, (6) interrogative about function, (7) interrogative about existence, (8) interrogative about reason, (9) interrogative about place, (10) interrogative about direction, and (11) interrogative about person. The function of interrogatives in Minangkabau language at Koto Tangah district Padang city, found in 7 functions, they are (1) used for ask about something, (2) used for rhetorical sentences, (3) used for confirmed the sentences, (4) used for ask for the opportunity, (5) used for satire sentence, (6) used for offers something, and (7) used for express the distrust.Â Keywords: Form, Function, Interogative